2023
DOI: 10.1097/jp9.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer with ovarian metastasis: cases report and literature review

Abstract: Background: Pancreatic cancer with ovarian metastases is rare and easily misdiagnosed. Patients with ovarian metastases are first diagnosed with ovarian cancer and may miss the opportunity to receive surgical operation. We report 7 rare cases of ovarian metastases secondary to pancreatic adenocarcinoma and review the literature to analyze clinical characteristics, diagnostic methods, and potential therapeutic strategies for the rare malignancy.Cases Summary: We retrospectively analyzed the clinical data of 7 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Zhang JJ et al reported 6 breast tumors metastatic in an ovary from 177 tumors identified, but the histological type was not specified, and the CA-125 level was higher than 35 U/L in 65% of the cases included in their study [7]. In the rest of the analyzed studies, isolated cases of ovarian metastases of breast lobular carcinoma or tumors with primary localization in other organs were reported [2][3][4]6,[8][9][10][11]. The types of primary tumors metastatic to the ovary, their incidence, CA-125 levels, and the number of cases identified in the literature database are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Zhang JJ et al reported 6 breast tumors metastatic in an ovary from 177 tumors identified, but the histological type was not specified, and the CA-125 level was higher than 35 U/L in 65% of the cases included in their study [7]. In the rest of the analyzed studies, isolated cases of ovarian metastases of breast lobular carcinoma or tumors with primary localization in other organs were reported [2][3][4]6,[8][9][10][11]. The types of primary tumors metastatic to the ovary, their incidence, CA-125 levels, and the number of cases identified in the literature database are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian metastases from breast cancer account for 3-30% of all ovarian ovarian neoplasms [1][2][3][4][5][6][7][8][9][10][11]. We identified both lobular and invasive ductal breast carcinoma studies with metastasis to the ovary, but the cases presented in the current literature data were We studied the biphasic tumor areas immunohistochemically and observed that the round cells were positive for AE-1/AE-3 cytokeratin, mammaglobin, and GCDFP-15, and the fusiform tumor cells stained for inhibin and calretinin (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations